2003
DOI: 10.1002/jemt.10340
|View full text |Cite
|
Sign up to set email alerts
|

Ectopic adrenocorticotropin (ACTH) and corticotropin‐releasing hormone (CRH) production in the adrenal gland: Basic and clinical aspects

Abstract: The hypothalamic-pituitary-adrenal (HPA) axis is integrated in the human stress system and controls the metabolism of many cell systems in the body. Therefore, hypofunction or hyperfunction of the HPA axis potentially threatens the life of the whole organism. Noncontrolled overproduction of its key regulators, CRH and ACTH, causes dysfunction of the stress system. Ectopic secretion of these compounds may be part of extraadrenal paraneoplastic syndromes caused by various benign or malignant tumors. However, ect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 51 publications
1
21
0
2
Order By: Relevance
“…This is similar to the situation in mammals where CRF and CRF-BP are present in the medulla, but not the cortex, of the adrenal gland (Nussdorfer 1996, Ehrhart-Bornstein et al 1998, Chatzaki et al 2002. The distribution of CRF in the chromaffin, but not the glucocorticoid compartment of vertebrates, is in agreement with their ontogenic roots: interrenal or adrenocortical cells are mesodermally derived, whereas the chromaffin cells originate from neural crest (Vrezas et al 2003). Apparently, the expression of neuropeptides or peptide hormones in the Figure 5 The effects of K C and 8-bromo-cAMP on the release of CRF and cortisol from superfused carp head kidneys.…”
Section: Discussionsupporting
confidence: 80%
“…This is similar to the situation in mammals where CRF and CRF-BP are present in the medulla, but not the cortex, of the adrenal gland (Nussdorfer 1996, Ehrhart-Bornstein et al 1998, Chatzaki et al 2002. The distribution of CRF in the chromaffin, but not the glucocorticoid compartment of vertebrates, is in agreement with their ontogenic roots: interrenal or adrenocortical cells are mesodermally derived, whereas the chromaffin cells originate from neural crest (Vrezas et al 2003). Apparently, the expression of neuropeptides or peptide hormones in the Figure 5 The effects of K C and 8-bromo-cAMP on the release of CRF and cortisol from superfused carp head kidneys.…”
Section: Discussionsupporting
confidence: 80%
“…It was shown, that the CRH is also produced at several extrahypothalamic sites including the adrenal medulla (Udelsman et al, 1986;Bruhn et al, 1987;Venihaki et al, 1997;Vrezas et al, 2003). Several authors demonstrated that adrenals express the CRH type 1 and 2 receptors Vrezas et al, 2003).…”
Section: Discussionmentioning
confidence: 98%
“…ACTH is mainly produced in the corticotropic cells from the anterior pituitary, but is also produced in the brain, adrenal medulla, skin, and placenta (Vrezas et al 2003, Bicknell 2008, Evans et al 2012. As ACTH is the most potent stimulus of the adrenal cortex, most of the knowledge on its mechanism of action derives from studies on the adrenal cortex or ACTH receptor-expressing cells.…”
Section: Introductionmentioning
confidence: 99%